2015
DOI: 10.1159/000375411
|View full text |Cite
|
Sign up to set email alerts
|

Is Immediate Radical Cystectomy Necessary for All Patients with Non-Muscle-Invasive Micropapillary Bladder Cancer?

Abstract: Introduction: We aim to review the outcomes of micropapillary urothelial carcinoma (MPUC) of the bladder from a single institution. The hypothesis is that non-muscle-invasive (NMI) MPUC may have a heterogeneous prognosis, and detailed pathological analysis may identify patients that could be managed without immediate cystectomy. Patients and Methods: This is a retrospective analysis of patients presenting with MPUC in a primary transurethral resection specimen (n = 40). The pattern of micropapillary (MP) diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 22 publications
0
12
0
1
Order By: Relevance
“…MPUC is associated with aggressive behavior and poor survival most probably due to frequent lymphatic invasion and metastases [5,15]. In comparison with MPUC of the upper urinary tract both malignancies present with similar aggressive characteristics [16].…”
Section: Discussionmentioning
confidence: 99%
“…MPUC is associated with aggressive behavior and poor survival most probably due to frequent lymphatic invasion and metastases [5,15]. In comparison with MPUC of the upper urinary tract both malignancies present with similar aggressive characteristics [16].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, controversies exist regarding the socalled non-invasive micropapillary component [98,112], which may be interpreted as micropapillary-like features in NMIBC and CIS, and therefore should not be classified as true MV [8,16,42,[113][114][115][116][117]. The pattern of superficial MV-UC has been associated with an improved OS when compared with invasive MP (63 vs. 47 months, p = 0.05) in an MV-NMIBC series managed conservatively [118]. In keeping with this, progression to T1 disease occurred in only 2 out of 16 patients with pTa MV-UC managed with surveillance in a recent series [119].…”
Section: Micropapillary Variantmentioning
confidence: 99%
“…Further, most of the specimens of patients who underwent deferred RC showed advanced disease after intravesical therapy with BCG suggesting no beneficial effect in this histological subtype ( 64 , 65 ). Recently Jackson et al aimed to identify patients who might be managed without immediate RC distinguished all non-muscle invasive MPBC tumors (n=40) into superficial (pTa) and invasive carcinomas (pT1) ( 66 ). Unsurprisingly, the authors reported that superficial MPBC is associated with higher survival rates (median OS 63 vs. 47 months), and concluded, that those might therefore be managed more conservatively with TUR-BT and possible deferred RC in selected patients ( 66 ).…”
Section: Micropapillary Carcinomamentioning
confidence: 99%
“…Recently Jackson et al aimed to identify patients who might be managed without immediate RC distinguished all non-muscle invasive MPBC tumors (n=40) into superficial (pTa) and invasive carcinomas (pT1) ( 66 ). Unsurprisingly, the authors reported that superficial MPBC is associated with higher survival rates (median OS 63 vs. 47 months), and concluded, that those might therefore be managed more conservatively with TUR-BT and possible deferred RC in selected patients ( 66 ). Still there is evidence that intravesical therapy is less effective in variants as compared to UC, with progression rates of up to 70% after 8 months, therefore advocating generously for early RC in all non-muscle invasive MPBC ( 14 , 63 ).…”
Section: Micropapillary Carcinomamentioning
confidence: 99%